STUDY OF THE POSSIBLE ANTIHYPERTENSIVE AND HYPOLIPIDEMIC EFFECTS OF AN HERBAL MIXTURE ON L-NAME-INDUCED HYPERTENSIVE RATS - Abdel Salam, Mouchira; Mm Ibrahim, Bassant; El-batran, Seham; SOUAD E EL-GENGAIHI; Abou baker, Doha h (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Hypertension is a chronic medical condition. Diet can improve blood pressure control and decrease the risk of health complication. Methods: In this study, four plants: Roselle, Marjoram, Chamomile, and Doum were extracted by water. Equal portions of them were mixed. Lethal dose 50% of the mixture was assayed; the dose which did not cause any mortality was 266.94 mg/100 g body weight. Animals were classified into five groups: Negative control group, positive control group where hypertension was induced by L-name, two groups treated with two doses of the mixture, and a group treated with prazosin as a standard treatment. Treatment of hypertensive rats continued for 4 successive weeks. Results: Treatment with the mixture showed a significant reduction in blood pressure of hypertensive rats, as well as serum cholesterol, low-density lipoprotein-cholesterol, and urea levels when compared to positive control group. Conclusion: The results obtained suggest that the aqueous extract is efficient as an antihypertensive and hypolipidemic agent. Keywords: Rats, Aqueous extract, Hypertension, Hyperlipidemia, L-name.